Does corporate governance affect M&As’ impact on social and environmental performance? Evidence from Milan Stock Exchange’s listed firms - Alex Almici; Renato Camodeca; Luisa Bosetti (European Scientific Journal, ESJ, 2025)
This study’s aim is twofold: (1) to explore the effect of mergers and acquisitions (M&As) on bidders’ social and environmental performance, and 2) to determine the potential drivers of this process by focusing on corporate governance characteristics. The analysis is based on M&As performed by firms listed on the Milan Italian Stock Exchange during the 5-year period of 2018–2022. The research data were retrieved from the FactSet and Refinitiv Eikon databases and examined using regression analyses.  The findings demonstrate that M&As positively affect social and environmental performance, as long as good corporate governance practices are in place. The current research draws on stakeholder-agency theory and identifies the potential drivers of the value creation process in the M&A context enhancing the limited existing literature on this topic. The findings highlight the role of corporate governance in strengthening the impact of M&As on bidders’ non-financial performance, offering valuable practical implications. First, investors and financial analysts should develop a comprehensive perspective to assess the M&A’s impact on non-financial performance. Second, regulators should consider strengthening specific corporate governance requirements. Finally, policymakers should encourage M&As undertaken by firms with sustainability-oriented boards of directors.